Faktor yang mempengaruhi partisipasi konsumen pada pemasaran media sosial - Riska, Riska (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The influence of social media marketing activities is very influential on shopping intentions in Indonesia. Not much has been done on social media marketing activities for Wardah cosmetics, so this researcher will focus on Wardah cosmetic products by analyzing the effect of social media marketing activities on the spending intentions of the Indonesian people during the post-pandemic period. The aim of this study is to influence social media marketing activity and customer experience on purchase intention, loyalty, and participation through relationship quality in social commerce. The population of this study is all customers who purchase Wardah products in North Jakarta. Purposive sampling technique with age range respondents is not limited. Data analysis used a purposive sampling technique with the Structural Equation Modeling Partial Least Square (SEM-PLS) method. Based on the test results, it can be seen that the marketing program carried out by Wardah is proven to be able to make the quality of the relationship between the Wardah brand and consumers have a good attachment. This attachment is caused by marketing communications that use social media marketing activities appropriately. This conclusion shows that social media marketing activities can form a good awareness relationship between the Wardah brand and Wardah consumers.